ANALISIS KESALAHAN PESERTA DIDIK KELAS VIII SMPN 1 PAYAKUMBUH DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI POLA BILANGAN BERDASARKAN ANALISIS KESALAHAN NEWMAN - Bunga Levinda (Jurnal Edukasi dan Penelitian Matematika, 2020)
Error analysis is one of the effective methods to identify patterns of mathematical errors of students. This research aims to describe and analyze the students' mistakes at VIII SMPN 1 Payakumbuh in solving math essay-tests on the number pattern using Newman’s error analysis. The errors studied were based on the types of errors in the Newman error indicator which include reading errors, comprehension error, transformation error, process skill error, encoding error. This descriptive research used qualitative approach. This type of research is descriptive with research subjects as many as 5 students of class VIII.3 SMPN 1 Payakumbuh based on students who have the most errors and different variation of errors. The result showed the percentage reading errors is , comprehension error is , transformation error is , process skill error is  and encoding error is .Keywords – Error Analysis, Newman’s Error Analysis, Number Pattern